Trade in healthcare and health insurance services: The GATS as a supporting actor (?) - Rudolf Adlung (World Trade Organization (WTO), 2009)
The General Agreement on Trade in Services (GATS) is broader in policy coverage than conventional trade agreements for goods and, at the same time, offers governments more flexibility, in various dimensions, to tailor their obligations to sector- or country-specific needs. An overview of existing commitments on healthcare and health insurance services shows that WTO Members have made abundant use of these possibilities. While most participants elected not to undertake bindings on healthcare services at the end of the Uruguay Round, nor to make offers in the ongoing negotiations, insurance services have been among the most frequently committed sectors. If there is a common denominator, regardless of the Members concerned (except for recently acceded countries), it is the existence of a lot of 'water' between existing commitments and more open conditions of actual access in many sectors. This may also explain, in part, why there have been very few trade disputes under the GATS to date - far fewer than under the GATT in merchandise trade. Also, governments appear to be generally hesitant in politically and socially sensitive areas to take action in the WTO. There are indications, however, that the same 'players' have acted differently in other policy contexts. For example, it appears that under recent preferential trade agreements (PTAs) the European Communities has been even more cautious in committing on hospital services and protecting scope for (discriminatory) subsidies than under the GATS. Yet, this is not necessarily true for the obligations assumed by many countries, including individual EC Member States, under bilateral investment treaties (BITs). These treaties overlap with the GATS, as far as commercial presence is concerned, and may be used by aggrieved investors to challenge policy restrictions in host countries. However, though frequently invoked, BITs do not meet the same standards, in terms of transparency, open (consensual) rulemaking and legal certainty, as commitments under the GATS.
Keywords: F13; F53; F59; I18; K33; 330; GATS; trade in services; international investment; public health; Außenhandel; Gesundheitsversorgung; Dienstleistung; Krankenversicherung; GATS; Handelsabkommen; Welt